DNA Probe Design for Detection Mutation at Codon 315 In katG Gene of Mycobacterium Tuberculosis to Real-Time Polymerase Chain Reaction - Rahmaryani, I Gusti A. A. Santhi; Ariani, Ni Kadek; Warma Dewi, Dyah Subadrika; Ani, Ni Komang Sasi; Sundari, Ade Ari; Hartati, Kadek Widya Yuli; Yowani, Sagung Chandra (Journal of Health Sciences and Medicine, 2018)
High-level resistance to isoniazid as a first-line tuberculosis drugs can be caused by mutations in codon 315 katG Mycobacterium tuberculosis . Mutation at codon 315 is the most frequent mutation with the highest amino acid variation, compared to other codons in the Mycobacterium tuberculosis katG   gene. Therefore, a specific probe   is required for rapid and proper detection of mutations at codon 315. In this study, the design of a nucleotide sequence probe with TaqMan labeling was performed using Clone Manager Suite 6 software . The mutant probe   obtained was analysed in two stages. The initial analysis is based on the length of the probe   (22-30 bases), Tm (70ºC), %GC (35-65%), not in hairpin   form, dimer   (< 5 bases), runs   and repeat   (? 4 for base A, T, C, and < 3 for base G). Furthermore the final analysis was carried out with no G base in 2 bases at the end of the 5’ probe   and the amount of base C ? G. The study resulted in 260 probe mutants. After the initial analysis, 11 mutant probes were obtained to recognize mutations in the codon of 315 katG Mycobacterioum tuberculosis   genes. The probe   consists of 2 probes   for the S315T mutation, 6 probes for S315N mutation, and 3 probes   for S315V mutation. The criteria of the 11 mutant probes   are 22-23 bases long, Tm 70ºC, % GC 56-63%, 4 dimer , 2 runs , and does not have repeats   and does not form hairpin   at a temperature of 56ºC. Based on the final analysis, 3 mutant probes   were obtained fulfilling the TaqMan probe labeling criteria, namely K315MT1 for specific detection of mutation S?T and K315MN5, then K315MN23 for specific detection of mutation S?N. The conclusion of this study shows that the best mutant nucleotide sequence probes for the detection of mutations at codon of 315 KatG Mycobacterium tuberculosis   genes are 5’-FAM-CC ACC GGC ATC GAG GTC GTA TG-TAMRA-3’; 5’FAM-ATC ACC AAC GGC ATC GAG GTC G-TAMRA-3’; dan 5’FAM-C ACC AAC GGC ATC GAG GTC GTA T-TAMRA-3’. The design of the mutant probe according to the TaqMan probe criterion for real-time PCR was obtained by 3 probes from the 11 selected mutant probes in the initial analysis.